MODEL SISTEM TAFSIR TAWHIDI IBN BARRAJAN DALAM MENAFSIRKAN AYAT-AYAT KAWNIYYAH - Ah. Haris Fahrudi (MIYAH : Jurnal Studi Islam, 2024)
Abstract: The Qur'an mentions many natural phenomena (al-âyat al-kawniyyah) so that humans take lessons from them. Unfortunately, classical interpretations do not give enough attention to it. One of the classical interpretations that gives attention to it is the interpretation of Ibn Barrajân, the Andalusian mufasir and Sufi figure of the 16th century H. Sufi interpretations that reveal many non-literal dimensions of the Qur'an have been seen as a form of deviation from the standard interpretation of the Qur'an or only as an emotional expression that is subjective, given / mawhibah and therefore not iterative. This article discusses Ibn Barrajân's Sufistic interpretation of the âyât kawniyyah through a systems approach. With this approach, Ibn Barrajân's interpretation is seen as a system by identifying the elements of the system in it. This research extends two discernible conclusions: First, Ibn Barrajân's Sufi interpretation is a system of interpretation that transforms the sources of interpretation as input into a holistic interpretation (al-tafsîr al-tawhîdî) as its output through the integral cognitive process of the mufasir consisting of tauhid paradigm, methodology and competence of the mufasir. Second, Ibn Barrajân's system of interpretation is an open system that interacts with its environment so that it is dynamic. Keywords: sistem tafsir, tafsir sufi, Ibn Barrajân, ayat kawniyyah